2017
DOI: 10.11604/pamj.2017.27.229.12853
|View full text |Cite
|
Sign up to set email alerts
|

Primary hydatid cyst of the pancreas of the child: a case report

Abstract: Primary pancreatic hydatid lesions are very rare with an incidence of less than 1% in the adult population. We report an observation of a 5-year-old girl who consulted for isolated abdominal pain occurring for 2 weeks without vomiting, transit disorders or jaundice and evolving in a context of conservation of the general condition and apyrexia. Clinical examination and preoperative imaging have suggested the diagnosis of a choledochal cyst or duodenal duplication rather than a hydatid cyst of the pancreas due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…They are rare, with an incidence rate ranging from 0.14% to 2% [ 5 ]. They are exceptionally reported in children [ 6 ]. Pancreatic cyst grows slowly at a rate of 0.3-2 cm/year [ 7 ], and their size is variable from few millimeters to several centimeters [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are rare, with an incidence rate ranging from 0.14% to 2% [ 5 ]. They are exceptionally reported in children [ 6 ]. Pancreatic cyst grows slowly at a rate of 0.3-2 cm/year [ 7 ], and their size is variable from few millimeters to several centimeters [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are exceptionally reported in children [ 6 ]. Pancreatic cyst grows slowly at a rate of 0.3-2 cm/year [ 7 ], and their size is variable from few millimeters to several centimeters [ 6 ]. In 90% of cases, PHCs are solitary; they are located in the pancreatic head in 50-58% of the cases [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary hydatid disease of the pancreas is rare-the largest single study of hydatid disease in 357 cases occurring over 20 years had only 1 case [9]. Infestation of the pancreas occurs mainly by hematogenous or peri-pancreatic lymphatic invasion [10]. Clinical manifestation depends on the anatomical location of cyst and its complications such as infection, rupture, hemorrhage, biliary or pancreatic fistula, vascular thrombosis and acute or chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…7 In another interesting case, authors reported pancreatic hydatid cyst in a patient presented with abdominal pain and jaundice. 8 Therefore, the disease can mimic a number of clinical conditions. In Wei et al's study, the disease mimicked renal cell carcinoma.…”
mentioning
confidence: 99%